2018
DOI: 10.1177/0269215518785945
|View full text |Cite
|
Sign up to set email alerts
|

Comparing disability between traumatic brain injury and spinal cord injury using the 12-item WHODAS 2.0 and the WHO minimal generic data set covering functioning and health

Abstract: Both generic measures were able to detect severe disability but also to detect differences between two patient populations with different underlying diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
11
0
3
Order By: Relevance
“…Previous studies of WHODAS 2.0 in stroke patients have usually been based on a longer version of this scale (36). The aim of the current study was to identify as simple validated functioning scales as possible, and the 12-item WHODAS 2.0 was found suitable, especially as, in previous studies among patients with amyotrophic lateral sclerosis, traumatic brain injury, spinal cord injury and spinal pain (20)(21)(22)(23)(24), this measure was easy to apply for both patients and significant others. As WHODAS includes not only activities, but also items of participation, it provides a wider perspective for goal-setting and service-planning than the conventional instruments.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies of WHODAS 2.0 in stroke patients have usually been based on a longer version of this scale (36). The aim of the current study was to identify as simple validated functioning scales as possible, and the 12-item WHODAS 2.0 was found suitable, especially as, in previous studies among patients with amyotrophic lateral sclerosis, traumatic brain injury, spinal cord injury and spinal pain (20)(21)(22)(23)(24), this measure was easy to apply for both patients and significant others. As WHODAS includes not only activities, but also items of participation, it provides a wider perspective for goal-setting and service-planning than the conventional instruments.…”
Section: Discussionmentioning
confidence: 96%
“…To unify the assessment of functioning globally, regardless of health condition, the World Health Organization (WHO) has developed a generic patient-and proxy-reported instrument to measure both activities and participation, the WHO Disability Assessment Schedule (WHODAS 2.0), which has been validated in various conditions, including stroke (18). The short 12-item form of WHODAS 2.0 has been found to be practical for use in various clinical settings (19)(20)(21)(22)(23)(24). Another short ICF-based instrument, the 7-item WHO Minimal Generic Set of domains of functioning and health, has been suggested for use as a starting point to address comparability of data across studies (25).…”
mentioning
confidence: 99%
“…Many previous studies focused on the medical problems and treatment of CNS injuries [14,15], while measures of activity and participation for community-dwelling people with chronic CNS injuries remain relatively underdeveloped. Several studies evaluated the activity and participation of people with CNS injuries, and compared the pattern of disability between different disease groups [16][17][18][19][20]. Some previous studies employed WHODAS 2.0 to study various health conditions, including stroke, TBI, SCI, and aging.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies employed WHODAS 2.0 to study various health conditions, including stroke, TBI, SCI, and aging. Two studies compared functioning and disability between TBI and SCI groups [16,17], and another compared the disability level between amyotrophic-lateral-sclerosis and TBI groups [18]. Studies with institutionalized individuals suggested that institution-dwelling is related to poor functioning [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Priorities in developing appropriate functioning instruments for patients with SCI include understanding the dimensions of participation, and the importance of both objective and subjective measures (10). Only a few studies, however, have tested participation instruments, such as WHODAS 2.0, in individuals with SCI, and there is still a lack of studies comparing self-rated functioning with more objectively defined parameters (14)(15)(16)(17)(18)(19). Other difficulties in measuring functioning lie in a redundancy of instruments for different health conditions and tools that are too time-consuming for clinical settings.…”
mentioning
confidence: 99%